2021
DOI: 10.1016/j.isci.2021.102339
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal protein SIC activates monocytes and induces inflammation

Abstract: Summary Streptococcus pyogenes is a major bacterial pathogen in the human population and isolates of the clinically important M1 serotype secrete protein Streptococcal inhibitor of complement (SIC) known to interfere with human innate immunity. Here we find that SIC from M1 bacteria interacts with TLR2 and CD14 on monocytes leading to the activation of the NF-κB and p38 MAPK pathways and the release of several pro-inflammatory cytokines (e.g. TNFα and INFγ). In human plasma, SIC binds c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Monocytes and dendritic cells were increased in the blood of participants who developed pharyngitis. Activation of monocytes to induce proinflammatory responses occurs following binding of TLR2 to the Streptococcal Inhibitor of Complement (SIC) protein secreted by S. pyogenes which may explain the elevated intermediate monocyte frequency 30 . In addition, the elevation of monocytes and dendritic cells was associated with increased levels of IL-1Ra, IL-18 and IP-10, produced in response to infection [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes and dendritic cells were increased in the blood of participants who developed pharyngitis. Activation of monocytes to induce proinflammatory responses occurs following binding of TLR2 to the Streptococcal Inhibitor of Complement (SIC) protein secreted by S. pyogenes which may explain the elevated intermediate monocyte frequency 30 . In addition, the elevation of monocytes and dendritic cells was associated with increased levels of IL-1Ra, IL-18 and IP-10, produced in response to infection [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…CEF might also have additional yet undiscovered binding partners apart from complement proteins similar to SIC which also inhibits the antibacterial activity of a wide range of antimicrobial peptides and proteins, including lysozyme, LL-37 and human beta-defensins [ 52 ]. SIC also interacts with both human thrombin and plasminogen to inhibit fibrinolysis [ 53 ] and with Toll-like receptor 2 (TLR-2) and CD14 on monocytes to induce pro-inflammatory cytokines [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sic has several different mechanisms of actions, interference with complement and other host defences, and has been proposed to play a significant role in streptococcal infections [ 57 ]. It was recently shown that the Sic protein from M1 S. pyogenes , a type over-represented among severe invasive cases of NSTI [ 20 ], interacts with TLR2 resulting in release of pro-inflammatory cytokines [ 58 ]. A study by Kachroo et al [ 59 ] revealed a positive correlation between sic and genes involved in the host immune response and inflammation when they examined the dual RNA-seq transcriptomes of S. pyogenes and host skeletal muscle from infected non-human primates.…”
Section: Discussionmentioning
confidence: 99%